Reinvestment Risk and the Equity Term Structure - GONÇALVES, ANDREI S. (Journal of Finance, 2021)
ABSTRACT The equity term structure is downward sloping at long maturities. I estimate an Intertemporal Capital Asset Pricing Model (ICAPM) to show that the trade‐off between market and reinvestment risk explains this pattern. Intuitively, while long‐term dividend claims are highly exposed to market risk, they are good hedges for reinvestment risk because dividend prices rise as expected returns decline, and longer‐term claims are more sensitive to discount rates. In the estimated ICAPM, reinvestment risk dominates at long maturities, inducing relatively low risk premia on long‐term dividend claims. The model is also consistent with the equity term structure cyclicality and the upward‐sloping bond term structure.